Application of Academic Papers in Formulation Legal Products at the Regional - Antari, Putu Eva Ditayani; Fadli, Moh.; Negara, Tunggul Anshari Setia; Susmayanti, Riana (Journal of Law, Society, and Islamic Civilization, 2023)
The formation of legal products in the regions cannot be separated from the preparation of academic texts as the basis for their formation. However, the existence of alternative explanations/information as a substitute for academic texts has caused legal products at the regional level not to fully use academic texts. Based on this, it is necessary to elaborate on the urgency of academic papers in the formation of legal products at the regional level. In addition, further explanation regarding the mechanism for implementing academic papers in the formation of legal products at the regional level is the main research objective. The research method used in research is normative legal research or doctrinal legal research which bases arguments on theories, principles, concepts, and laws and regulations. The selection of the normative method is based on the existence of legal issues regarding the blurring of norms regarding the regulation of academic texts in the formation of legal products at the regional level. An explanation of this can only be obtained by conducting a doctrinal study. The results of the research lead to the conclusion that academic papers are needed as guidelines in drafting legal products at the regional level. Implementation of academic drafting should be carried out in the pre-legislative stage by identifying problems in society and elaborating them theoretically so that solutions can be formulated as outlined in the draft legal products at the regional level. The preparation of academic manuscripts also requires collecting data through interviews, observations, and literature studies to find solutions to problems in society. These results then go through a dissemination process in the form of FGDs with community representatives and parties related to the regional regulations that will be formed.